Improvement in Mathematics Learning Outcomes in ‎Fraction Operation Material with Grid Square Unit Media - Asha Septianti Nur Rohmah (Prodi PGMI IAIN Salatiga, 2019)
This research was motivated by MI Ma'arif Kutowinangun fifth grade students who have difficulty in receiving the lessons with materials related to addition and subtraction of various fractions. Especially, when dealing with addition and subtraction of fractions operations with different denominators. This was showed by the results of interviews and observations made by the author. With minimum completeness criteria of 60, from 14 students of V class, only nine of them reached the minimum completeness criteria, and the rest have not been able to achieve the minimum completeness criteria.Based on the above problems, then the author conducted Classroom Action Research (CAR) to determine the improvement of mathematics learning outcomes in fraction operation material with grid square unit media. The research subject was fifth grade students of MI Ma’arif Kutowinangun consisting of 20 students, 11 of them were female and nine of them were male. While, the data collection was obtained through interviews, observation, and evaluation results through written tests which then were analyzed by percentage.Based on this research, there was improvement of student mathematics learning outcomes in fraction operation with grid square unit media. From 20 students who reached the minimum completeness criteria 60 in the first cycle was 16 students or 80%. Then it increased in the second cycle that all fifth grade students of MI Ma'arif Kutowinangun reached the minimum completeness criteria or 100%.